Advances and trends in microbial production of polyhydroxyalkanoates and their building blocks - Gao, Qiang; Yang, Hao; Wang, Chi; Xie, Xin-Ying; Liu, Kai-Xuan; Lin, Ying; Han, Shuang-Yan; Zhu, Mingjun; Neureiter, Markus; Lin, Yina; Ye, Jian-Wen (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid development of synthetic biology, a variety of biopolymers can be obtained by recombinant microorganisms. Polyhydroxyalkanoates (PHA) is one of the most popular one with promising material properties, such as biodegradability and biocompatibility against the petrol-based plastics. This study reviews the recent studies focusing on the microbial synthesis of PHA, including chassis engineering, pathways engineering for various substrates utilization and PHA monomer synthesis, and PHA synthase modification. In particular, advances in metabolic engineering of dominant workhorses, for example Halomonas, Ralstonia eutropha, Escherichia coli and Pseudomonas, with outstanding PHA accumulation capability, were summarized and discussed, providing a full landscape of diverse PHA biosynthesis. Meanwhile, we also introduced the recent efforts focusing on structural analysis and mutagenesis of PHA synthase, which significantly determines the polymerization activity of varied monomer structures and PHA molecular weight. Besides, perspectives and solutions were thus proposed for achieving scale-up PHA of low cost with customized material property in the coming future.